Improving Chemistry Learning Outcomes for Vocational Students Using ARIAS Learning Model - Panjaitan, Sriwidya Hotmaria; Hartono, Hartono; Dharmansyah, Eddy (Jurnal Pendidikan Progresif, 2018)
Improving chemistry learning outcomes for vocational students using ARIAS learning model. Objectives: This classroom action research was carried out to investigate students’ chemistry learning outcomes at vocational level through ARIAS learning model. Methods: The study was conducted in two cycles, each cycle consisting of two meetings. Findings: The mean score before the treatment (T0) was 66.89 with learning mastery percentage of 40.54%, then the mean score increased to 76.51 after teacher applied ARIAS learning model in cycle I (T1) with learning mastery percentage of 62.16%. The improvement of the mean score of students’ cognitive learning outcomes also occurred in the last cycle. The mean score of student cognitive test result was 84.09 with learning mastery percentage of 89.19%. Students also gave positive responses of learning process Keywords: Classroom action research, ARIAS learning model, chemistry learning outcomes DOI: http://dx.doi.org/10.23960/jpp.v8.i2.201801